Summary of ISO/TC 201 International Standard ISO 18516:2019 Surface chemical analysis—Determination of lateral resolution and sharpness in beam‐based methods with a range from nanometres to micrometres and its implementation for imaging laboratory X‐ray photoelectron spectrometers (XPS). (22nd October 2021) - Unger, Wolfgang E. S.; Senoner, Mathias; Stockmann, Jörg M.; Fernandez, Vincent; Fairley, Neal; Passiu, Cristiana; Spencer, Nicholas D.; Rossi, Antonella
Abstract : ISO 18516:2019 Surface chemical analysis—Determination of lateral resolution and sharpness in beam‐based methods with a range from nanometres to micrometres revises ISO 18516:2006 Surface chemical analysis—Auger electron spectroscopy and X‐ray photoelectron spectroscopy—Determination of lateral resolution . It implements three different methods delivering parameters useful to express the lateral resolution: (1) the straight edge method, (2) the narrow line method and (3) the grating method. The theoretical background of these methods is introduced in ISO/TR 19319:2013 Surface chemical analysis—Fundamental approaches to determination of lateral resolution and sharpness in beam‐based methods . The revised International Standard ISO 18516 delivers standardized procedures for the determination of the (1) effective lateral resolution by imaging of square‐wave gratings, the (2) lateral resolution expressed as the parameter D 12–88 characterizing the steepness of the sigmoidal edge spread function (ESF) determined by imaging a straight edge and (3) the lateral resolution expressed as the full width of half maximum of the line spread function (LSF), w LSF, determined by imaging a narrow line. The last method also delivers information on the shape of the LSF, which characterizes an individual imaging instrument. Finally, the implementation of all three standardized methods in the field of imaging laboratory X‐ray photoelectron spectroscopy (XPS) is shortly presented. This part of the letter is based on the use of a new test sample developed at ETH Zurich, Switzerland. This test sample displays a micrometre scaled pattern motivated by the resolving power of recent imaging XPS instruments.